2016
DOI: 10.1108/so-05-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

HR outsourcing trends in Malaysia: the undetected tiger

Abstract: Purpose The purpose of this study is to provide deeper and broader insights into human resource outsourcing (HRO) trends and practices specific to the Malaysian context. Design/methodology/approach Data were collected from HR managers through a questionnaire-based survey, using convenient sampling with random selection. Findings HRO practices were found to have evolved into second-generation outsourcing, with considerable potential to grow further in the future. Firm size and sector had little or no effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
(106 reference statements)
0
9
0
Order By: Relevance
“…For example, Smith et al (1998) posit that the most critical objective in information system outsourcing to firms is cost reduction. Sim et al (2016) assert that cost is one of the major drivers of human resource outsourcing in Malaysia. Benson (1999) studied outsourcing, organizational performance and employee commitment in Australian manufacturing firms, and the result showed that four companies had achieved significant cost reduction.…”
Section: Theoretical Foundation a Model Of The Research And Hypotheses Developmentmentioning
confidence: 99%
“…For example, Smith et al (1998) posit that the most critical objective in information system outsourcing to firms is cost reduction. Sim et al (2016) assert that cost is one of the major drivers of human resource outsourcing in Malaysia. Benson (1999) studied outsourcing, organizational performance and employee commitment in Australian manufacturing firms, and the result showed that four companies had achieved significant cost reduction.…”
Section: Theoretical Foundation a Model Of The Research And Hypotheses Developmentmentioning
confidence: 99%
“…For the future, it is also anticipated that HRO outsourcing leaders are companies that have been deficient in HRO discussions in the past. For example, over the next ten years, more outsourcing is expected by these companies (Sim et al, 2016).…”
Section: K 499mentioning
confidence: 99%
“…From the findings that others had gathered over the years, companies that outsource some or most of their nonessential functions have been able to concentrate most of their valuable resources towards achieving competitive advantage. In a world economy that is highly interdependent today, outsourcing of jobs is a natural trend 25 found that HRO practices have evolved into second-generation outsourcing, with considerable potential to grow further in the future. Firm size and sector had little or no effect on the degree of HRO.…”
Section: Findings and Conclusionmentioning
confidence: 99%